Modeling and optimization of cutting parameters when turning EN-AW-1350 aluminum alloy - Khrouf, F.; Tebassi, Hamid; Yallese, M.A.; Chaoui, Kamel; Haddad, A. (Zielona Góra: Uniwersytet Zielonogórski)
An experimental investigation is carried out to examine the effects of various cutting parameters on the response criteria when turning EN-AW-1350 aluminum alloy under dry cutting conditions. The experiments related to the analysis of the influence of turning parameters on the surface roughness (Ra) and material removal rate (MRR) were carried out according to the Taguchi L27 orthogonal array approach.
Keywords: ANOVA; Artificial Neural Networks (ANN); chip shape; optimization; response surface methodology